2019
DOI: 10.2174/1381612825666190619145025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy and Death Pathways in Dose-dependent Isoproterenolinduced Cardiotoxicity

Abstract: Background:Isoproterenol (ISO) is a non-selective β-adrenergic agonist. Our aims were to investigate the autophagy and cell death pathways including apoptosis and necrosis in ISO-induced car-diac injury in a dose-dependent manner.Methods:Male Sprague-Dawley rats were treated for 24 hours with I. vehicle (saline); II. 0.005 mg/kg ISO; III. 0.05 mg/kg ISO; IV. 0.5 mg/kg ISO; V. 5 mg/kg ISO; VI. 50 mg/kg ISO, respectively. Hearts were isolated and infarct size was measured. Serum levels of Troponin T (TrT), lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Potential mechanisms depicted in Figure 3 show that reperfusion of the ischemic myocardium intensifies the incidence of reperfusion-induced arrhythmias, which are followed by necrosis-, apoptosis-, and autophagy-induced cell deaths (Osipov et al, 2009;Zhang et al, 2012;Chang et al, 2013;Czegledi et al, 2019;Gyongyosi et al, 2019;Yasuda et al, 2019). From a different point of view, autophagic processes may be even beneficial, depending on their intensity in reversible injured myocardial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms depicted in Figure 3 show that reperfusion of the ischemic myocardium intensifies the incidence of reperfusion-induced arrhythmias, which are followed by necrosis-, apoptosis-, and autophagy-induced cell deaths (Osipov et al, 2009;Zhang et al, 2012;Chang et al, 2013;Czegledi et al, 2019;Gyongyosi et al, 2019;Yasuda et al, 2019). From a different point of view, autophagic processes may be even beneficial, depending on their intensity in reversible injured myocardial cells.…”
Section: Resultsmentioning
confidence: 99%
“…From a different point of view, autophagic processes may be even beneficial, depending on their intensity in reversible injured myocardial cells. However, necrosis-induced cell death could dominate and mask autophagic signal transduction processes and autophagyinduced cell death in myocardial tissues (Czegledi et al, 2019;Gyongyosi et al, 2019). Cellular biology and genetics have a real value and significant impact to try better to define the generation of cardiovascular diseases, including life threatening cardiac arrhythmias.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, animal studies have shown that onset of ventricular fibrillation increases autophagy-associated proteins in the ventricle accompanied by myocardial damage [24][25][26], suggesting that arrhythmia itself may directly cause altered cardiac autophagy.…”
Section: Altered Autophagy In the Atrium In Chronic Afmentioning
confidence: 99%
“…Isoproterenol is an extensively employed non-selective β-adrenergic agonist. It was suggested that at small dose of isoproterenol, autophagy may cope with the toxic arrhythmic effect of isoproterenol [123]. It is anticipated that non-invasive interventions such as exercise might be the countermeasure to arrhythmogenesis.…”
Section: Mitophagy and Exercisementioning
confidence: 99%